2018
DOI: 10.2147/ijgm.s179206
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization rate and outcomes in patients with left ventricular dysfunction receiving hemodialysis

Abstract: IntroductionLeft ventricular dysfunction (LVD) is characterized as left ventricular ejection fraction (EF) below half of the systolic capacity of the left ventricle. Patients on hemodialysis have higher risk of developing LVD than the general population. Our aim was to assess hospitalization rate and outcomes in hemodialysis patients with LVD.Patients and methodsAll patients ≥18 years old, who started hemodialysis therapy at King Abdulaziz University Hospital between January 2011 and December 2011, were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
1
1
1
Order By: Relevance
“…Studies have shown that HD patients with CHF have a higher hospitalization risk [18,20]. However, in our study, the all-hospitalization risk was similar among HD patients with and without CHF.…”
Section: Discussioncontrasting
confidence: 74%
“…Studies have shown that HD patients with CHF have a higher hospitalization risk [18,20]. However, in our study, the all-hospitalization risk was similar among HD patients with and without CHF.…”
Section: Discussioncontrasting
confidence: 74%
“…We found only two studies addressing echocardiographic findings among ESKD patients in KSA and no other previous studies among KTRs were found. Albeshri et al studied 333 Saudi HD patients and demonstrated that LV dysfunction (EF <40) was associated with higher morbidity and mortality rates when compared with patients with normal EF [ 38 ]. In another single-center study of 192 Saudi patients, Sharabas et al showed that PD patients had higher urine output and better Kt/V values, however, they were more edematous and using more antihypertensive medications and had a lower EF [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Распространенность артериальной гипертензии у пациентов на программном гемодиализе (ГД), по данным диализных центров, достигает 95% [1]. В условиях отсутствия адекватной коррекции артериальная гипертензия является независимым фактором риска гипертрофии левого желудочка, запускающим механизм патологического ремоделирования миокарда еще на начальных стадиях хронической болезни почек [2]. Структурные изменения миокарда приводят к ухудшению его функции, клиническими последствиями являются нарушения ритма сердца и прогрессирование хронической сердечной недостаточности [3].…”
unclassified